Anatolian J Cardiol 2022
DOI: 10.5152/anatoljcardiol.2021.933
|View full text |Cite
|
Sign up to set email alerts
|

Advancement in Coronary Angiography or Percutaneous Coronary Intervention Using the Distal Transradial Artery Access in Acute Coronary Syndrome and Complex Coronary Artery Disease

Abstract: As the incidence of coronary heart disease increases annually, coronary angiography and percutaneous coronary intervention procedures are also increasing. The femoral artery and radial artery paths are commonly used for percutaneous coronary intervention, but their clinical application is limited to a certain extent due to many postoperative complications. The distal transradial access path is a new surgical path for coronary angiography and percutaneous coronary intervention. In this study, we reviewed the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Blind intubation without measuring artery diameter may be associated with a higher risk of arterial injury [15]. Our study found that patients with artery diameter smaller than the sheath had obvious resistance during the placement of the sheath, pushing the guide wire and sending the guide catheter, and patients felt obvious discomfort during removal of the catheter [16]. The reason for this occurrence may be that the abundant alpha-adrenergic receptors in the outer vascular membrane of the artery make the radial artery prone to have higher vascular reactivity, which contributes to tem-porary and sudden vascular narrowing after local trauma [17].…”
Section: Discussionmentioning
confidence: 67%
“…Blind intubation without measuring artery diameter may be associated with a higher risk of arterial injury [15]. Our study found that patients with artery diameter smaller than the sheath had obvious resistance during the placement of the sheath, pushing the guide wire and sending the guide catheter, and patients felt obvious discomfort during removal of the catheter [16]. The reason for this occurrence may be that the abundant alpha-adrenergic receptors in the outer vascular membrane of the artery make the radial artery prone to have higher vascular reactivity, which contributes to tem-porary and sudden vascular narrowing after local trauma [17].…”
Section: Discussionmentioning
confidence: 67%
“…In the emergency context, the dTRA puncture time is a concern as it may delay the D-to-B time. A review about dTRA in STEMI indicated that the puncture time of the dTRA did not affect the timely opening of the culprit vessel [ 18 ]. Kim Y reported that the mean snuffbox puncture time was 2.7 ± 1.6 min in patients with STEMI, which did not delay the D-to-B time [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, patients in the DRA group had shorter fluoroscopy times, total radiation doses, and hospitalization days, and patients in the TF group had a higher mortality rate during hospitalization (0% in the dTRA group and 18% in the TF group, p = 0.013). 58 Cao et al’s review showed that the puncture time for coronary angiography or PCI using the DRA path for ACS is 28.63 s to 162 ± 96 s. 59 As a perspective, the option of using large bore catheters in complex high-risk coronary cases remains open and must be tested with DRA 60 ; for example, a 2.0 mm rotablation burr requires an 8-French catheter and not all arterial lumens support such a size. In this case, the role of ultrasound becomes relevant again by means of preoperative assessment of arterial diameter because the incidence of RAO is directly related to the ratio between the sheath and artery size.…”
Section: Distal Radial Access For Coronary Interventionsmentioning
confidence: 99%